Methodical features of physical rehabilitation of victims with consequences of mine and explosive trauma - Дандаш, Хассан; Подкопай, Денис Олегович (Slobozhanskyi Herald of Science and Sport, 2016)
Khassan Dandash, Pidkopai D. Purpose: the analysis of modern approaches to application of means and forms of physical rehabilitation of victims with mine and explosive trauma at an out-patient stage. Material & Methods: the analysis of actual special references on a problem of the mechanism of defeat, treatment and rehabilitation of consequences of mine and explosive trauma. Results: it is defined that the percent of use of nonconventional methods of non-drug therapy increases objectively and significantly in the last decade in physical rehabilitation along with a broad application of traditional complex techniques of medical physical culture, massage and physical therapy. Conclusions: kinesiotherapy, hydro-bathing technologies, reflexotherapy are most demanded in practical techniques of physical rehabilitation at mine and explosive trauma for today among methods of non-drug therapy.